2022
DOI: 10.1055/a-1910-4339
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Digitization on the Safe Management of Anticoagulants

Abstract: Background: Anticoagulants are high-risk medications and are a common cause of adverse events of hospitalised inpatients. The incidence of adverse events involving anticoagulants has remained relatively unchanged over the past two decades, suggesting novel approaches are required to address this persistent issue. Electronic medication management systems (eMMS) offer strategies to help reduce medication incidents and adverse drug events, yet poor system design can introduce new error types. Objective: To evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Program director 1 Clinical informatics director and Consultant endocrinologist 4 Full text free online at australianprescriber.tg.org.au EDITORIAL of a clinical analytics product alone. To truly transform practice, clinical decision support must become embedded into clinical workflows and be accepted by busy clinicians.…”
Section: Clair M Sullivanmentioning
confidence: 99%
See 2 more Smart Citations
“…Program director 1 Clinical informatics director and Consultant endocrinologist 4 Full text free online at australianprescriber.tg.org.au EDITORIAL of a clinical analytics product alone. To truly transform practice, clinical decision support must become embedded into clinical workflows and be accepted by busy clinicians.…”
Section: Clair M Sullivanmentioning
confidence: 99%
“…The number of patients experiencing a bleed decreased significantly (mean 12.1/month versus 7.8/month, p=0.01). 4 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an early study by Bates et al 7 in inpatients found that medical errors decreased by 86% when a range of CDS features including drug allergy and drug-drug interaction warnings among others were implemented. More recently, a study by Austin et al 8 found that the implementation of an EHR system can improve the clinical outcomes of patients requiring management of their anticoagulant medications. However, the implementation of CDS must be balanced, as having too many alerts can cause alert fatigue.…”
Section: Background and Significancementioning
confidence: 99%